Coronavirus disease (COVID-19) and disseminated intravascular coagulation syndrome - A. D. Makatsariya; K. N. Grigoreva; M. A. Mingalimov; V. O. Bitsadze; J. Kh. Khizroeva; M. V. Tretyakova; I. Elalamy; A. S. Shkoda; V. B. Nemirovskiy; D. V. Blinov; D. V. Mitryuk (IRBIS LLC, 2020)
COVID-19 is an infectious disease caused by the beta-coronavirus SARS-CoV-2 that in 2020 has spread worldwide. In most severe patients, the clinical picture begins with respiratory failure further deteriorating up to multiple organ failure. Development of coagulopathy is the most adverse prognostic. Analyzing currently available clinical data revealed that 71.4 % and 0.6 % of survivors and fatal cases, respectively, demonstrated signs of overt disseminated intravascular coagulation (DIC). Monitoring D-dimer level, prothrombin time, platelet count and fibrinogen content is important for determining indications for treatment and hospitalization in COVID-19 patients. In case such parameters deteriorate, a more pro-active "aggressive" intensive care should be applied. Low molecular weight heparin (LMWH) should be administered to all patients with diagnosed COVID-19 infection (including non-critical patients) requiring hospitalization, but having no contraindications to LMWH.